Peran Motivasi dalam Memoderasi Pengaruh Kecerdasan Emosional, Keseimbangan Kehidupan Kerja, Kepemimpinan, dan Etos Kerja terhadap Kinerja Karyawan - Yusniar Lubis; Fajar Rezeki Ananda Lubis; Syaifuddin Syaifuddin; Nasib Nasib (Society, 2023)
This research assesses the direct and indirect impact of emotional intelligence, work-life balance, leadership, and work ethics on employee performance at the Camait office in Central Tapanuli Regency, North Sumatra. Employing a quantitative analytic approach, the study sampled 146 workers, from which 88 employees were selected using the Slovin formula. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that emotional intelligence, work-life balance, leadership, and motivation directly, positively, and significantly impact employee performance. In contrast, work ethic does not significantly affect employee performance. Moreover, motivation is a moderating variable that can indirectly influence the relationships between work-life balance, leadership, work ethic, and employee performance. However, motivation alone cannot effectively moderate the relationship between work ethic and employee performance at the Central Tapanuli Regency Head Office. This study underscores the importance of enhancing emotional intelligence, achieving a better work-life balance, and cultivating effective leadership to boost employee performance. Furthermore, it highlights the crucial role of motivation as a moderating factor in improving overall job performance. However, it emphasizes that motivation should be complemented with other strategies to address work ethic issues effectively.